2021
DOI: 10.1016/j.cegh.2021.100902
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco quitting during COVID-19: A mixed-methods pilot study among participants screened for a cessation trial in India

Abstract: Introduction: COVID-19 and subsequent country-wide lockdown has impacted smokeless tobacco (SLT) product availability in India. We aimed to examine SLT quitting during COVID-19 lockdown among SLT users who consented to be enrolled in a cessation programme. Methods: Between January-March 2020, we screened 227 exclusive SLT users to be enrolled in a randomizedcontrolled feasibility study on SLT cessation. However, all activities were suspended due to national lockdown in response to the COVID-19 pandemic. To exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While unavailability and over pricing of SLT products motivated some to attempt quit or reduce use, financial crisis due to unemployment, caused by the pandemic, forced some to quit. Similarly, price rise and lesser availability of SLT products during lockdown period were observed to be important factors in quitting among SLT users enrolled in a cessation trial in India (Singh et al, 2021) as well as in other studies on tobacco use (Giovenco et al, 2021;Gupte et al, 2020). These findings suggest the need for banning and increasing rates or taxes of tobacco products which could perhaps help in the control of SLT use.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…While unavailability and over pricing of SLT products motivated some to attempt quit or reduce use, financial crisis due to unemployment, caused by the pandemic, forced some to quit. Similarly, price rise and lesser availability of SLT products during lockdown period were observed to be important factors in quitting among SLT users enrolled in a cessation trial in India (Singh et al, 2021) as well as in other studies on tobacco use (Giovenco et al, 2021;Gupte et al, 2020). These findings suggest the need for banning and increasing rates or taxes of tobacco products which could perhaps help in the control of SLT use.…”
Section: Discussionmentioning
confidence: 59%
“…Apart from this, there were concerns about SLT being identified as a risk factor in COVID-19 infection (Gaunkar et al, 2020) as using SLT often involved hand-to-mouth contact and the virus could be transmitted when a user spits out saliva produced during the chewing process. Studies from India as well as abroad suggested complex drivers and mechanisms associated with COVID-19 lockdown that impacted SLT consumption (Gupte et al, 2020;Singh et al, 2021;Anderson, 2022). The lockdown more specifically resulted to decreasing use of SLT due to the closure of tobacco sales and/or isolation from social circles (Grover et al, 2020;Arora et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This disease can increase susceptibility to squamous cell carcinoma. 29 , 30 Similarly, a prognostic role of fibrinogen has been proposed for OSCC. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings also indicate that more attention to the COVID-19 pandemic could help decrease cigarette consumption and enhance quitting intention, which is consistent with previous studies 14,24 . This is possible because high levels of COVID-19 attention could result in more related news seeking, from which smokers may improve their understanding of the risk of smoking and the importance of cessation during the pandemic [25][26][27][28] . Thus, media should take the role of informing the public about the risk of smoking during the pandemic.…”
Section: Discussionmentioning
confidence: 99%